Plant image analysis : fundamentals and applications - Gupta, S. Dutta; Ibaraki, Yasuomi (CRC Press/Taylor and Francis, 2014)
The application of imaging techniques in plant and agricultural sciences had previously been confined to images obtained through remote sensing techniques. Technological advancements now allow image analysis for the nondestructive and objective evaluation of biological objects. This has opened a new window in the field of plant science. Plant Image Analysis: Fundamentals and Applications introduces the basic concepts of image analysis and discusses various techniques in plant imaging, their applications, and future potential.
Keywords: Image analysis.; Phenotype.; Plants -- Analysis.; elektronické knihy; electronic books